Catalyst‐ and Supporting‐Electrolyte‐Free Electrosynthesis of Benzothiazoles and Thiazolopyridines in Continuous Flow. Issue 2 (6th December 2017) - Folgueiras‐Amador, Ana A.; Qian, Xiang‐Yang; Xu, Hai‐Chao; Wirth, Thomas
Abstract: A catalyst‐ and supporting electrolyte‐free method for electrochemical dehydrogenative C−S bond formation in continuous flow has been developed. A broad range of N ‐arylthioamides have been converted to the corresponding benzothiazoles in good to excellent yields and with high current efficiencies. This transformation is achieved using only electricity and laboratory grade solvent, avoiding degassing or the use of inert atmosphere. This work highlights three advantages of electrochemistry in flow, which is (i) a supporting electrolyte‐free reaction, (ii) an easy scale‐up of the reaction without the need for a larger reactor and, (iii) the important and effective impact of having a good mixing of the reaction mixture, which can be achieved effectively with the use of flow systems. This clearly improves the reported methods for the synthesis of benzothiazoles. Abstract : No catalyst and no supporting electrolyte are needed for the formation of benzothiazoles from N ‐arylthioamides. Electrons and a flow reactor for electrochemistry are sufficient.